Investigating the Architectural Structure and Decorations of Aligholi Agha School Mosque in Isfahan - Mohieddin Aghadavoudi (Journal of Global Pharma Technology, 2017)
School mosques, as places where the science and worship are blended, have a particular position in Safavid era Isfahan’s style of architecture; and, the study and recognition of such places is of a great importance in terms of their associated architectural structure and decorations. Among these, Aligholi Agha School-Mosque as the most important building in Aligholi Agha urban collection should be recounted as one of the aforementioned buildings featuring prominent points regarding the structure and decoration which is the significant theme dealt with in the format of the current research paper. Thus, the most important question raised herein is that what are Aligholi Agha school mosque characteristic architectural structure and decoration features? The present study is based on a descriptive-analytical method and the information has been collected based on field observations and library research. Also, the findings have been analyzed based on quantitative methods. The results of the current study confirm that Aligholi Agha blended structure, while being small in its dimensions, encompasses distinct decorations and inscriptions turning it into a tiny treasure of the Safavid Era treasure. Among the most important of these decorations and ornamentations are the embossed tiles embedded with geometrical and plant-like carvings on the façade and the sceneries bestowed upon the interior spaces. Also, there are diverse inscriptions made via seven-color techniques and mosaic and stone carvings by taking advantage of buildings’ Kufi style of writing and Nasta’alygh calligraphy bearing contents such as the representation of Holy Quran’s Ayat and Hadith, compliments and praising king Sultan Hussein, information about the construction and an introduction on the personality of Aligholi Agha as the founder of the building.Keywords: Safavid era architecture, structure, decorations, Aligholi Agha school mosque